MEDICINAL PLANTS AND PHYTOTHERAPEUTICS: A REFLECTION ON TOXIC AND THERAPEUTIC EFFECTS - do Carmo, Taynara Michelato; de Souza, Bianca Silva; da Cruz, Gabriela Campos de Melo; de Souza, Yuri Matheus; Bohm, Franciele Mara Lucca Zanardo (Editora Impacto Científico, 2025)
The consumption of medicinal plants and herbal medicines for the treatment of a wide range of illnesses has been growing as an alternative to traditional medicine. The reasons for consuming these plants include ease of access, fewer side effects, low cost, lack of prescriptions, and even cultural or religious beliefs. However, both herbal remedies and medicinal plants can cause a variety of undesirable reactions, such as poisoning, nausea, irritation, edema, and even death, like any other medication. The objective of this study was to identify the medicinal and toxic effects of medicinal plants and herbal medicines. The methodology consisted of a survey of articles published between 2009 and 2025 on the topic in the search engines Scielo, Google Scholar, and Web of Science using the following keywords: medicinal plants, toxic properties, phytotherapy, clinical effects. The search results yielded 1,590 papers. Studies that lacked scientific evidence of toxic or therapeutic effects, or that did not address the research topic, were excluded. Eighteen articles citing more than forty medicinal plants and herbal remedies remained. To refine this article, the searches were then repeated using the scientific names of the plants previously described to complement the work and provide further insight into their toxicity. Medicinal plants and herbal remedies obtained through their processing, extraction, and the production of teas, ointments, gels, etc., have vast uses for health promotion. However, it is important to be aware of their toxic effects. Choosing a medicinal plant for consumption requires understanding its toxicity, whether through incorrect administration or even the choice of plant. Therefore, it is crucial to promote the safe use of medicinal plants and herbal remedies, as well as to raise awareness of the risks of toxicity. DOI: https://doi.org/10.56238/edimpacto2025.060-016